SISTEM APLIKASI LAYANAN ADMINISTRASI DESA BERBASIS ANDROID - Mohammad Alvi Fauzil Akbar; Izzatul Umami; Winarti Winarti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Population service is one of the most important tasks in a government agency such as a village, especially in a modern era like today, demands for accurate information that is obtained quickly and easily. Bareng Village is a village with a population of approximately 2,655 people, thus the administrative service process for letter application services can cause queues and does not rule out the possibility of typing errors in the applicant's identity in the submitted letter. This can also cause delays in processing letters and can hinder the issuance of letters, because the number of village employees on duty is limited to only a few people, while the number of letter applicants exceeds the working capacity of village employees. To overcome this problem, it is necessary to have a village administration application that can help service letter requests for the community to be faster and more accurate. In this study, an android-based Bareng village administration service application was built. This research uses a systems approach method, namely the Rational Unified Process (RUP), and the system development method uses the UML method. The results of this study are the application of Bareng village government administration services that can make it easier for residents to get information about the village and provide information on the status of completion of certificates, as well as appropriate village inventory data